The Effect of Using Accounting Information, Business Manager Interest and Level of Understanding on the Success of Small and Medium Enterprises (Study on Culinary Business of Cirebon City) - Dilah Bunga Melani; Diva Andina; Lya Fadillah; H Roni Mulyatno (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Based on the phenomenon that accounting practices in SMEs are still very low, but financial management in SMEs should require good accounting skills by the business owner. The required application system is the Accounting Information System. The object of this study is the Culinary SMEs in Cirebon City, West Java.The population in this study is culinary business owners in Cirebon City, West Java, which is as many as 1075 culinary entrepreneurs according to Cirebon Satu Data 2022. While the sample in this study was set at 92 culinary entrepreneurs with sampling measured using a formula to determine the sample size (Yamane, 1970) Purposive sampling is the sampling strategy utilized in this study. SMEs with historical business management records meet the sample requirements. Primary data are the data type employed in this investigation. The utilization of accounting information has been shown to positively impact the success of culinary SMEs in Cirebon City, West Java, according to the results of the hypothesis test that was conducted. The attainment of corporate success is significantly influenced by accounting information. Among other things, planning and supporting decision-making in corporate management are two areas in which accounting information may help. It is clear from the discussion's outcomes that using accounting information has an impact on a company's ability to succeed in.